DESIGNING ENGLISH AND SCIENCE GAME IN ANDROID AS TEACHING MATERIAL TO SUPPORT CLIL APPROACH - Mulyono, Paksi Jati; ., Ikhsanudin; Salam, Urai (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract : This research is to design a game as material to support Content Language Integrated Learning Approach(CLIL) which is applied on Science subject on 5th grade students of Cerdas Istimewa class on SD Muhammadiyah 2 Pontianak. The method of this research is development research that uses ADDIE instructional development procedure (Analysis, Design, Development, Implement, dan Evaluation). The result of this research is a game that helps students to learn the specific science term or basic vocabulary in lifecycle topic of science subject. The game has been already evaluated by expert in media and learning. As the result, the media expert evaluation is 4.65 that is classified as feasible to be used as instructional media. The result of the subject matter evaluation is 4.29 that mean feasible to be used as supplementary material to support the CLIL approach for Science subject. Keyword: Designing Material, Game, CLIL approach. Abstrak: Penelitian ini bertujuan untuk mendesain sebuah game android yang berguna sebagai material untuk membantu pendekatan Content Language Integrated Learning (CLIL) yang diterapkan pada pelajaran IPA pada siswa Cerdas Istimewa kelas 5 di SD Muhammadiyah 2 Pontianak. Adapun metode penelitian yang digunakan adalah penelitian pengembangan dengan tahapan ADDIE (Analysis, Design, Development, Implement, dan Evaluation). Hasil dari penelitian ini adalah sebuah game yang berperan sebagai material pembantu (scaffolding) yang dapat membantu siswa untuk belajar kata-kata dasar dalam topik pelajaran siklus kehidupan di pelajaran sains. Game tersebut telah di evaluasi oleh expert di bidang pembelajaran dan media. Alhasil, game ini dikatakan layak dengan skor 4.29 pada tinjauan media dan 4.65 pada tinjauan pembelajaran. Kata Kunci: Mendesain Materi, Game, Pendekatan CLIL. Â